Plant Protease Inhibitors: A Defense Mechanism Against Phytophagous Insects - Kumar, Dr. Manoj (Journal for Research in Applied Sciences and Biotechnology, 2024)
In the realm of agriculture, the constant threat of pests and pathogens poses a significant challenge to crop yields. Traditional chemical pesticides, while effective, come with drawbacks such as lack of specificity and the development of resistance. This has spurred a growing interest in exploring alternative methods, with a focus on biodegradable biological control agents and natural products. One promising avenue is the use of Plant Protease Inhibitors (PPIs), which act as a defense mechanism against phytophagous insects. PPIs hinder the activity of insect gut digestive enzymes, leading to reduced protein digestion and impeding the growth and survival of insects. The article delves into the various types of PPIs, their mechanisms of action, and their effectiveness in plant defense. Specifically, it explores the Cystatin Superfamily, with a focus on Family–4 Cystatins known as Phytocystatins. These inhibitors, found in a variety of plants, exhibit potential as biopesticides due to their impact on insect proteolysis. The study also discusses the role of phytocystatins in controlling phytophagous arthropods by targeting their essential digestive proteases. In conclusion, the article emphasizes the significant value of phytocystatins in plant defense and suggests their potential integration as a novel tool in Pest Control Management, highlighting the need for improved policies to enhance their adoption in sustainable agriculture.